Edukasi Adaptasi Perilaku Kerja Generasi Z pada Mahasiswa Fakultas Ekonomi dan Bisnis - Elly Noer; Okto Irianto; Tini Adiatma; Jacobus Rico Kuntag; Dodhy Hyronimus Ama Longgy; Adi Maulana Rachman; Ni Luh Putu Nita Yulianti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Generation Z is now starting to enter the world of work, where this generation has different characteristics from other generations. This Community Service aims to educate generation Z who are students about adapting to work behavior in the world of work for students at the Faculty of Economics and Business. The method of delivering this education is carried out by conducting webinars using virtual meetings which are carried out involving several higher education institutions in Indonesia and Malaysia, where they have previously collaborated. This activity is considered effective in providing students with an understanding of how students who are Generation Z must be able to adapt in the world of work. This activity deserves to be held again, considering the enthusiasm of the webinar participants in the question and answer session.